Temporal trends of acute kidney injury in patients undergoing percutaneous coronary intervention over a span of 12 years. (25th November 2020) - Skalsky, K; Bental, T; Vaknin-Assa, H; Assali, A; Greenberg, G; Codner, P; Samara, A; Ben Gal, T; Eisen, A; Kornowski, R; Perl, L
Abstract: Background: Acute kidney injury (AKI) is a known complication following percutaneous coronary intervention (PCI), and is associated with higher rates of complications. We sought to determine the potential impact of temporal changes on the rates of AKI over time, as well as possible determinants of risk. Methods: From a large prospective registry of patients undergoing PCI, 20, 032 consecutive patients were assessed at two time periods: 2006–2012 and 2012–2018. Of these, included were cases for which data existed regarding change in creatinine levels from baseline to 48 hours after PCI. AKI was defined according to two methods- a relative elevation of ≥25% in serum creatinine or an absolute elevation of ≥0.5 mg/dL in serum creatinine at 48 hours. Results: 15, 153 patients were available for final analysis, 7, 913 in the first period and 7, 240 in the second. Mean age was 65.0y and 66.0y (p<0.01) and baseline creatinine was 1.08 mg/dL and 1.15 mg/dL respectively (p<0.01, table 1). AKI according to 25% relative rise in serum creatinine was documented in 11.1% in the early period and in 7.3% of the patients in the late period, p<0.01. According to the definition of 0.5 mg/dL absolute rise in serum creatinine, respective rates were 3% and 2.9%, p=0.82 (figure 1). Multivariate analysis demonstrated a lower risk of AKI in the late period (OR- 0.72; CI 0.61–0.85, P<0.01). Factors associated with risk of AKI included reduced ejection fraction (OR-0.98; CI 0.976–0.99, p<0.01), older age (OR-1.01; CI 1.005–1.02, p=0.01) and female gender (OR- 1.73; CI 1.46–2.06, p<0.01). Conclusions: We have witnessed an improvement in the rates of post-PCI AKI over time. Further research is warranted, to further reduce peri-procedural AKI. Funding Acknowledgement: Type of funding source: None